Game theory in action : an introduction to classical and evolutionary models - Schecter, Stephen (Professor of mathematics); Gintis, Herbert (Princeton University Press, 2016)
Game Theory in Action is a textbook about using game theory across a range of real-life scenarios. From traffic accidents to the sex lives of lizards, Stephen Schecter and Herbert Gintis show students how game theory can be applied in diverse areas including animal behavior, political science, and economics. The book's examples and problems look at such fascinating topics as crime-control strategies, climate-change negotiations, and the power of the Oracle at Delphi. The text includes a substantial treatment of evolutionary game theory, where strategies are not chosen through rational analysis, but emerge by virtue of being successful. This is the side of game theory that is most relevant to biology; it also helps to explain how human societies evolve. Aimed at students who have studied basic calculus and some differential equations, Game Theory in Action is the perfect way to learn the concepts and practical tools of game theory. Aimed at students who have studied calculus and some differential equationsExamples are drawn from diverse scenarios, ranging from traffic accidents to the sex lives of lizardsA substantial treatment of evolutionary game theoryUseful problem sets at the end of each chapter.